以马内利二校初中一年级学生使用 MICROSOFT TEAMS 对汉语学习的影响 - Novi Savitri Buana; Lily Thamrin; Tjen Veronica (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2022)
AbstractMicrosoft Teams (MT) is a full-featured chat-based collaboration platform, that integrates chat, video conferencing, file storage and more. In order to understand the impact of using the Microsoft Teams application on learning Mandarin, and the responds of the first-year secondary Immanuel junior high school students using Microsoft Teams on learning Mandarin, the writer used a questionnaire and survey method to obtain research result. The first result is the average rate of students using MT software is 73.4%, which proved that students using MT software can help students learn Chinese. And the average rate of students' response to using MT software to learn Chinese is 69.3%. It proved that the students have received the approval of using the MT software, which means that the students are satisfied with using the MT software to learn Chinese. The second result is the students' responds of using Microsoft Teams software on learning Mandarin are very interesting and satisfying; Student do tasks are more convenient to submit and also student can review the mandarin material easier because it is uploaded to Microsoft Teams.Keywords: Influence, Learning Chinese, Microsoft Teams software